The Physical Universe - Beiser Arthur (MC Graw Hill, 2008)
This is an outstanding text with a long history that has been updated and given a fresh look. The 2010 copyright year represents the 50th anniversary of the publishing of this classic text. The text is also accompanied by strong media component with the Connect online homework system, "CPS" eInstruction student response system questions, more extensive online quizzing, and PowerPoint lectures. Aimed at presenting the essentials of physics, chemistry, earth science, and astronomy in a clear, easy-to-understand way, The Physical Universe shows students how science works, how scientists approach problems, and why science constantly evolves in its search for understanding. The text can also be packaged with its long time companion student study guide, which includes a review of chapter terms and concepts; self quizzing for extra practice; and solved problems from the text.